Estimating a model of subjective financial well-being among college students - Sabri, Mohamad Fazli; Falahati, Leila (Center for Promoting Ideas, 2012)
The issue of financial well-being among college students has received increasing attention. The purpose of this study is to examine the association between childhood consumer experience, financial socialization, financial literacy, financial management and subjective financial well-being of college students. Data were collected from eleven public and private universities across Malaysia. Structural equation modeling indicated that childhood consumer experiences such as savings habits, primary socialization agents such as parents, sibling and even religion and secondary socialization agents such as peer and media contribute to students’ financial literacy level which the effect of secondary socialization agents was negative. Financial literacy has the greatest effect on financial management which in turn enhanced the perceived level of financial well-being among students. Overall, implications and recommendations for future research, teaching, and public policy are also provided for parents, college administrators, counselors, and educators.